The Nalachampu, or, Damayantī kathā : with the Viṣamapada prakāśa commentary by Chaṇḍapāla - Trivikramabhaṭṭa, 10th cent (SAMP early 20th-century Indian books project ;, 1932)
Poem in mixed prose and verse, on Nala and Damayantī, mythological characters; includes Viṣamapadaprakāśa commentary of Caṇḍapāla.